ANALYSIS OF CULTURAL TRANSMISSION AND DEVELOPMENT OF EDUCATIONAL INSTITUTIONS - Shintia Dwi Putri; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Education in the broadest sense is an influential life Promoting human development and progress, and education in a broader sense. In short, it is the process of improving one's ability to be better in various ways, including through the teaching process. According to Law no. 20 of 2003 In the national education system, education is a conscious and planned effort to create a learning atmosphere and learning process that makes students proactive. Develop self-potential, have religious spiritual strength, self-control, personality, intelligence, noble character and skills that people need. Educational activities are teaching activities that make a person understand, with this understanding, one can develop by applying the learned potential. Education is also inseparable from cultural factors and scope. Culture is the result obtained by humans in the process of interacting with the physical and non-physical environment in their lives.